Effect of fluctuations in salinity on anaerobic biomass and production of soluble microbial products (SMPs) - Stuckey, David C.; Vyrides, Ioannis (My University, 2009)
This study investigated the acclimation potential of batch fed anaerobic biomass with salinities of 0-50 gNaCl l-1. Anaerobic biomass was acclimatized to salinities up to 20 gNaCl l-1over a period of 35 days, with 3 consecutive feedings. After this period the biomass was subjected to non-saline conditions to simulate fluctuating feed compositions. High activity was obtained after the first exposure to non saline conditions for biomass previously exposed to 30 gNaCl l-1. Short exposure (2-48 h) to high salinity (40 gNaCl l-1) did not reduce biomass activity when it was re-subjected to normal conditions. The sensitivity of each anaerobic bacterial group showed that propionate utilisers were the most affected by sudden changes in salinity. Using size exclusion chromatography (SEC) it was found that biomass exposed to concentrations of salinity above 30 gNaCl -1 produced higher molecular weight soluble microbial products (SMPs) which were present in the culture for longer periods than the control indicating that the effluent was more difficult to degrade. With the sudden removal of salinity anaerobic biomass can easily readapt to normal conditions without any high MW compounds being produced. These findings highlight the fact that anaerobic biomass is able to overcome sharp decreases in salinity in contrast with aerobic biomass as reported in the literature.
Keywords: Anaerobic biomass; Recovery from salinity; Bacterial sensitivity to salinity; Soluble microbial products; Sodium inhibition